A Labdane Diterpene from Enicosanthum congregatum - Mohd Sirat, Hasnah; A. Hadi, A. Hamid (Universiti Putra Malaysia Press, 1993)
A labdane diterpene was isolated from the air-dried leaves of Enicosanthum congregatum. The structure has been established as 8,I6-dihydroxy-ent-Iabd-13en- 15-oic lactone on the basis of spectroscopic data.